2020
DOI: 10.1161/jaha.119.015013
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Apnea‐Hypopnea Index, a Measure of Obstructive Sleep Apnea Severity, for Atrial Fibrillation in Patients With Hypertrophic Cardiomyopathy

Abstract: Background Obstructive sleep apnea ( OSA ) is common and independently associated with atrial fibrillation ( AF ) in patients with hypertrophic cardiomyopathy ( HCM ). This study aimed to investigate the relationship between apnea‐hypopnea index ( AHI ), a measure of OSA severity, and prevalence of AF in a large series of patients with HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Despite improvements of pharmacological, surgical and interventional therapies in management of HCM, patients are at risk for a number of adverse events such as progressive heart failure, arrhythmias and sudden death 2 4 . Recently, increasing evidences from our works 5 , 6 and others 7 , 8 showed that obstructive sleep apnea (OSA) is extremely common among patients with HCM, with a prevalence ranging from 32 to 71%. OSA is independently associated with cardiac remodeling 9 , atrial fibrillation 5 and ventricular arrhythmias 10 which are risk factors for cardiac death in patients with HCM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite improvements of pharmacological, surgical and interventional therapies in management of HCM, patients are at risk for a number of adverse events such as progressive heart failure, arrhythmias and sudden death 2 4 . Recently, increasing evidences from our works 5 , 6 and others 7 , 8 showed that obstructive sleep apnea (OSA) is extremely common among patients with HCM, with a prevalence ranging from 32 to 71%. OSA is independently associated with cardiac remodeling 9 , atrial fibrillation 5 and ventricular arrhythmias 10 which are risk factors for cardiac death in patients with HCM.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increasing evidences from our works 5 , 6 and others 7 , 8 showed that obstructive sleep apnea (OSA) is extremely common among patients with HCM, with a prevalence ranging from 32 to 71%. OSA is independently associated with cardiac remodeling 9 , atrial fibrillation 5 and ventricular arrhythmias 10 which are risk factors for cardiac death in patients with HCM. Therefore, screening and management of OSA have great potential to improve clinical outcomes in HCM.…”
Section: Introductionmentioning
confidence: 99%
“…3). Diverse studies reported an association between cardiac hypertrophy and the severity of OSA [22, 23]. In addition, it is important to address that RH may lead to cardiac hypertrophy [24].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Chronic OSA induces sympathetic activation followed by a structural and electrical remodeling of the atria contributing to the AF maintenance and recurrence of AF paroxysms [ 84 ]. Higher AHI is a known factor associated with persistent or permanent AF [ 85 ].…”
Section: Endothelial Function After Treatment With Cpap In Specific Subgroupsmentioning
confidence: 99%